The Prediction of Distribution of the Invasive Fallopia Taxa in Slovakia - Petra Gašparovičová; Michal Ševčík; Stanislav David (Plants, 2022)
Invasive species are now considered the second biggest threat for biodiversity and have adverse environmental, economic and social impacts. Understanding its spatial distribution and dynamics is crucial for the development of tools for large-scale mapping, monitoring and management. The aim of this study was to predict the distribution of invasive Fallopia taxa in Slovakia and to identify the most important predictors of spreading of these species. We designed models of species distribution for invasive species of Fallopia—Fallopia japonica—Japanese knotweed, Fallopia sachalinensis—Sakhalin knotweed and their hybrid Fallopia × bohemica—Czech knotweed. We designed 12 models—generalized linear model (GLM), generalized additive model (GAM), classification and regression trees (CART), boosted regression trees (BRT), multivariate adaptive regression spline (MARS), random forests (RF), support vector machine (SVM), artificial neural networks (ANN), maximum entropy (Maxent), penalized maximum likelihood GLM (GLMNET), domain, and radial basis function network (RBF). The accuracy of the models was evaluated using occurrence data for the presence and absence of species. The final simplified logistic regression model showed the three most important prediction variables lead by distances from roads and rails, then type of soil and distances from water bodies. The probability of invasive Fallopia species occurrence was evaluated using Pearson’s chi-squared test (χ<semantics><msubsup><msubsup>2</msubsup>1</msubsup></semantics>). It significantly decreases with increasing distance from transport lines (χ<semantics><msubsup><msubsup>2</msubsup>1</msubsup></semantics> = 118.85, p < 0.001) and depends on soil type (χ<semantics><msubsup><msubsup>2</msubsup>1</msubsup></semantics> = 49.56, p < 0.001) and the distance from the water, where increasing the distance decrease the probability (χ<semantics><msubsup><msubsup>2</msubsup>1</msubsup></semantics> = 8.95, p = 0.003).